Optimizing Water Hyacinth as Organic Fertilizer to Support Zero Waste and Green Economy Initiatives - Martono, Galih Hendro; Neny Sulistianingsih; Ni Putu Sinta Dewi (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The overgrowth of water hyacinth (Eichhornia crassipes) in Batujai Dam, located in West Lombok Regency, has become a serious environmental concern. Its uncontrolled spread has disrupted water flow, limited irrigation functions, and negatively impacted aquatic biodiversity. However, instead of treating it as a problem, this community service activity focused on turning the weed into a helpful resource—specifically, a raw material for producing organic fertilizer. Purpose: The aim of this community service was to raise public awareness and provide training on managing water hyacinth sustainably while creating added value for the local economy. The program was conducted with a small-scale fertilizer producer in Central Lombok. Method: Using a Participatory Action Research (PAR) approach, the activity involved the local community at every stage—from identifying the issue, designing solutions, and implementing the processing techniques to evaluating the results together. This approach was chosen to build community ownership and ensure the continuity of the efforts after the program ended. Result: As part of the process, around 1,000 kilograms of water hyacinth were harvested, sun-dried, chopped, and composted using Trichoderma spp. After fermentation, the community produced 20 liters of liquid fertilizer and 400 kilograms of solid compost. Conclusion: Beyond its environmental impact, the activity opened up opportunities for alternative income and promoted the concept of zero waste. It also encouraged the community to see local ecological issues not as obstacles but as opportunities to support green and sustainable living.